Cost Volume Profit Analysis as a Profit Planning Tool at Buket Husnul - Hesti, Hesti; Aswat, Ibnu; Yunita, Khristina (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
UMKM Buket Husnul is a business in the creative industry that sells products in the form of flower bouquets with various models. In its profit planning Buket Husnul does not yet have a planning tool, therefore this study discusses related to profit planning at UMKM Buket Husnul which utilizes Cost-Volume-Profit analysis as a tool to plan its profits. Cost-Volume-Profit analysis is a very good profit planning tool to help business people make decisions in order to optimize their business profits. In this study, researchers used a type of research with descriptive qualitative methods, based on data sources from interviews and direct observation in the field. The research results of the cost volume profit analysis that have been carried out are for the contribution margin of Rp43,125,000.00 with a contribution ratio of 52%. In order to reach the break-even point or Break-Event- Point the business owner must be able to sell a bouquet of 1,100 units with an income of Rp. 8,269,231.00 per quarter so that the business does not get a loss, with the maximum Margin of Safety that can only decrease by Rp. 74,230,769.00 with a ratio of 89.98% and the results of Operating-Leverage of 1.12 times operating profit.